Effect the Size of Lead Particles on Gamma –Ray Absorption Coefficient - Bushra Majid Mahmood; Hameed Majid Mahmood (Peerian Journals Publishing, 2024)
The present work deals with the shielding properties of polymer composites using gamma rays emitted from (137Cs), narrow beam. Polymer composites with Lead in deferent size (powder and shot ball), in different lead weights ratio (0, 50, and 70) % wt as filler had been prepared. to clarify the difference in the spectrum absorption gamma rays through the process of exponential equations graphic performance of the count rate as a function of composite thickness. The incident and transmitted intensities were measured using gamma spectrometer incorporate Sodium Iodide with traces of Thallium Na I(Tl) scintillator detector. Linear attenuation coefficients (μ) for gamma ray were calculate. The experimental results show that gamma-ray attenuation coefficient is inversely proportional with the size of Pb particle size due to the reduction of the spaces between the lead particles. Results also indicated that the constructed materials show good radiation protection properties
Keywords: polymer; Lead; gamma-rays; liner attenuation coefficient